Aerosol Survival of Pasteurella tularensis Disseminated from the Wet and Dry States - Cox, C. S. (1971)
The aerosol survival in air and in nitrogen was measured for Pasteurella tularensis live vaccine strain, disseminated from the wet and dry states. The results showed that most of the loss of viability occurred in less than 2 min of aerosol age, i.e., a rapid initial decay followed by a much slower secondary decay. In nitrogen and air, minimum survival occurred at 50 to 55% relative humidity (RH) for wet dissemination and at 75% RH for dry dissemination. This shift indicated that aerosols produced by wet and dry dissemination were not equivalent and suggested that survival might not be related to bacterial water activity or content. The results showed that rehydration is the key process with regard to survival, but that lysis on rehydration is not a primary death mechanism. The effects of oxygen were complex because it could be either protective or toxic, depending upon other conditions. The protective action of oxygen was through an effect on the spent culture suspending fluid. The latter contained a toxic component, the activity of which is suppressed by oxygen; possibly the component is pumped away during freeze-drying. A toxic effect of oxygen was not found in the presence of spent culture media because the toxicity of the latter masks such an effect. With other bacterial suspending fluids, oxygen was shown to be toxic at low RH. Similar effects with regard to oxygen toxicity were also found with a laboratory strain of P. tularensis. Differences in oxygen toxicity for aerosols generated from the wet and dry states also suggest that bacterial water content and activity do not control aerosol survival.